Production of virgin coconut oil (VCO) via water soluble and centrifugation methods - Mohd Izzat Fida'iy, Mohamed (2010)
In this study, the potential of combination of water soluble material (chemical) and centrifugation method in demulsification (emulsion breaking) of coconut milk emulsion is investigated. The conventional methods to produce Virgin Coconut Oil (VCO) by using fermentation and cold pressing need longer time to break these emulsions. Coconut milk from the local market was used as samples for the study. The centrifuge speed was varied from 6000 to 12000 rpm and the centrifugation time process was tested for two times at centrifugation process for 30 and 90 min. The current research found that, centrifugation method can enhance the demulsification of oil-in-water (O/W) coconut milk emulsions in a very short time compared to the conventional methods. The experiment was conducted by assisted of water soluble material on centrifugation process in order to demulsified the coconut milk emulsion. Due to its fast and higher quality of Virgin Coconut Oil (VCO), water soluble and centrifuge can be used as an alternative demulsification method for oil-in-water coconut milk emulsions. This method provides higher yields, quicker and less expensive.